PENGARUH KONTEN TRAVEL BLOGGER TERHADAP KUNJUNGAN WISATAWAN DOMESTIK KE SUMBAWA - Rina Fitriana; Deivy Nasuition; Amaliya Amel (LONTAR: Jurnal Ilmu Komunikasi, 2020)
ABSTRACTOne of several ways for tourists to get various information about tourism is Travel Blogs that review different kinds of many interesting tourist destinations both in Indonesia and abroad. This study aims to determine which content that mostly increases domestic tourist visits to Sumbawa. This study takes a sample of 100 Travel Bloggers’ followers and used a descriptive correlational method, where the primary data were collected using questionnaires and observations and processed using validity, reliability, descriptive analysis, correlation coefficient tests, coefficient of determination tests, simple linear regression tests and hypothesis tests t. The results show that the Travel Bloggers’ content has a strong influence on the visit of domestic tourists to Sumbawa. The correlation coefficient between the two variables is catagorized in the interval 0.60 - 0.799, which is equal to 0.674 and therefore indicates a strong influence. Thus it can be concluded that the hypothesis test Travel Content variable (X) as a whole has a significant positive effect on tourist visits to Sumbawa (Y).